DETERMINATION OF INDICES TO THE METHOD OF CORRECTION OF THE PYELOURETERAL JUNCTION OBSTRUCTION ACCORDING TO THE DIURETIC ULTRASONOGRAPHY - Vorobets, D. (World of Medicine and Biology, 2015)
Indices to the minimally invasive transureteral endoscopic intrusions, as well as open or laparoscopic pyeloplasty based on indices of diuretic ultrasonography have been determined. Diagnostic significance of ultrasound diagnostics in determination of functional deficiency of ureter before the operation (according to the disadaptation of drainage function of the pelvis on the basis of forced diuresis) has been proved. It gives the possibility to substantiate differential approach to the choice of the method of surgical correction. It is shown that the average duration of complaints on pain and discomfort in the lumbar area of the lesion - 1.6 years among all patients with strictures; 1.4 years – in OPP group; 1.13 – in LPP group and 1.89 year - in the group, where endourological methods (BD, EPT, LR) were applicable. The open pyeloplastic and endoscopic surgeries (LR, BD and EPT) were performed almost equally often on the right and on the left, LPP was performed for correcting right PUJ twice as often as for the left. The episodes of hematuria occurred more frequently before selected palliative endoscopic methods of PUJ narrowing removal - endopyelotomy, balloon dilatation and laser resection. Dispersion of indicators of heterogeneous in its history and pathogenesis of disease PUJ strictures endoscopic surgery (EM) group, which includes patients for whom laser resection, balloon dilatation of stricture and endopyelotomy were planned, significantly differed only by the parameters of relative speed of post furosemide pelvis drainage and percentage growth of PUJ diameter. It is established that the diuretic ultrasonography in the ambulatory conditions enables to diagnose the organic nature of obstruction. An important condition for the effective treatment of hydronephrosis is an accurate diagnose of a reason for urodynamics violation and dynamic methods for determining of ureter pelvis area permeability and pelvis functionality significantly contribute to it. The boundaries of ultrasonography digital indicators of kidney pelvis and PUJ during forced diuresis at reasonable choice for surgery - open pyeloplasty, laparoscopic pyeloplasty endopyelotomy, laser dissection or PUJ balloon dilatation were determined . Ultrasonic parameters of urodynamics state in the PUJ area at different stages of hydronephrosis after various surgical interventions demonstrate the diagnostic significance of the study in determining the functional failure of ureter at preoperative phase (according to maladjustment drainage function of the pelvis at forced diuresis) were revised . Thus, it was shown that the reliable increase in velosity of post furosemide augmentation in the area under the pelvis segment stricture demonstrates the need for correction of the pathology. During this PUJ diameter in patients who were a subject to surgical treatment, was significantly lower and could not cope with an adequate urine diverting while forced diuresis (average difference with the sign "-"). Received statistical data confirm the correctness of candidates selection for the open pyeloplasty and dynamic monitoring group, and also show screenings similarities for open and laparoscopic pyeloplasty. Interesting was the absence of significant changes in increase of the area of the pelvis in 15 minutes after forced diuresis and reduction of the pelvis after 40 minutes, as well as in relative velosity of pelvis post furosemide drainage and PUJ diameter growth in 15 min after administration of furosemide between groups. That is, these parameters before palliative intervention not accurately reflected kidney dysfunction due to infra renal obstruction, which required correction and data renography supplement. However, the calculations of percentage increase in transversal pelvis area, speed of post furosemide area and pelvis drainage growth as well as measuring of the PUJ diameter before and after forced diuresis proved to be reliable differential instruments for surgical treatment due to indices (or their absence).